Waggle Dance Distances as Integrative Indicators of Seasonal Foraging Challenges - Couvillon, Margaret J. (Public Library of Science, 2014)
Even as demand for their services increases, honey bees (Apis mellifera) and other pollinating insects continue to decline in Europe and North America. Honey bees face many challenges, including an issue generally affecting wildlife: landscape changes have reduced flower-rich areas. One way to help is therefore to supplement with flowers, but when would this be most beneficial? We use the waggle dance, a unique behaviour in which a successful forager communicates to nestmates the location of visited flowers, to make a 2-year survey of food availability. We “eavesdropped” on 5097 dances to track seasonal changes in foraging, as indicated by the distance to which the bees as economic foragers will recruit, over a representative rural-urban landscape. In year 3, we determined nectar sugar concentration. We found that mean foraging distance/area significantly increase from springs (493 m, 0.8 km(2)) to summers (2156 m, 15.2 km(2)), even though nectar is not better quality, before decreasing in autumns (1275 m, 5.1 km(2)). As bees will not forage at long distances unnecessarily, this suggests summer is the most challenging season, with bees utilizing an area 22 and 6 times greater than spring or autumn. Our study demonstrates that dancing bees as indicators can provide information relevant to helping them, and, in particular, can show the months when additional forage would be most valuable.